2021
DOI: 10.3390/ani11092567
|View full text |Cite
|
Sign up to set email alerts
|

Is a Block of the Femoral and Sciatic Nerves an Alternative to Epidural Analgesia in Sheep Undergoing Orthopaedic Hind Limb Surgery? A Prospective, Randomized, Double Blinded Experimental Trial

Abstract: Peripheral nerve blocks are commonly used in human and veterinary medicine. The aim of the study was to compare the analgesic efficacy of a combined block of the femoral and sciatic nerves with an epidural injection of ropivacaine in experimental sheep undergoing orthopaedic hind limb surgery. Twenty-five sheep were assigned to two groups (peripheral nerve block; sciatic and femoral nerves (P); epidural analgesia (E)). In group P 10 mL ropivacaine 0.5% was injected around the sciatic and the femoral nerves und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The femoral-sciatic nerve block is a regional anaesthetic technique well described in small and farm animals. 7,[46][47][48][49][50] At present, few case reports have described this locoregional technique in different avian species: d'Ovidio et al described a nerve stimulator-guided femoral-sciatic nerve block in raptors undergoing surgical treatment of pododermatitis, while Trujanovic et al reported the same block in a duck undergoing surgical fixation of a tibiotarsal fracture guided by both ultrasound and nerve stimulator. In the present case, due to the small size of the animal, the ultrasonography visualisation of the femoral nerve was challenging, hence the decision of using the nerve stimulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The femoral-sciatic nerve block is a regional anaesthetic technique well described in small and farm animals. 7,[46][47][48][49][50] At present, few case reports have described this locoregional technique in different avian species: d'Ovidio et al described a nerve stimulator-guided femoral-sciatic nerve block in raptors undergoing surgical treatment of pododermatitis, while Trujanovic et al reported the same block in a duck undergoing surgical fixation of a tibiotarsal fracture guided by both ultrasound and nerve stimulator. In the present case, due to the small size of the animal, the ultrasonography visualisation of the femoral nerve was challenging, hence the decision of using the nerve stimulator.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we opted for a multimodal analgesic approach, which included the use of an opioid in premedication, as discussed above, combined with a local anaesthetic technique and ketamine infusion. The femoral‐sciatic nerve block is a regional anaesthetic technique well described in small and farm animals 7,46–50 . At present, few case reports have described this locoregional technique in different avian species: d'Ovidio et al.…”
Section: Discussionmentioning
confidence: 99%
“…In biomedical research, various procedures including orthopaedic, reproductive, cardiac, and abdominal surgeries are performed on sheep [7][8][9]. The use of pain relief in these procedures can ensure better animal welfare and higher ethical standards, promote the Three Rs, and minimise potential impacts on research outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of locoregional anaesthesia techniques for various surgical procedures, now commonplace in dogs and cats, has been reported in other species, including sheep [6], calves [7], goats [8,9], and pigs [10,11]. Local nerve blocks may be performed blind or guided by electrical nerve stimulation or ultrasound.…”
Section: Introductionmentioning
confidence: 99%